Enhancing ball passing creativity and effectiveness in youth women's football: A single-case study - Idarraga, J. F. V.; Valencia-Sánchez, W. G. (Journal of Physical Education and Sport, 2024)
The participation of women in soccer has increased, yet there is a notable lack of scientific growth in this area, particularly concerning the tactical and technical aspects. A didactic approach known as psychokinetic games (PGs) has been developed to enhance cognitive abilities, including concentration, attention, and anticipation. Consequently, this study aimed to assess the impact of PGs on tactical creativity, passing effectiveness, and ball control in youth women's soccer players. The study involved 10 female Colombian soccer players under the age of 14 from Club Deportivo Atlético Nacional (Medellín, Colombia), participating in the Antioquia Soccer League's First A division (n = 10; Mage = 13.1 ± 0.57 years; Mheight = 158 ± 6.74 cm; Mweight = 52.09 ± 5.98 kg; MIMC = 20.76 ± 2.05; Mfederated experience = 4.5 ± 3.1 years in soccer). These participants were classified as Tier 3 (highly trained/national level). The study employed a single-case design for manipulative strategy, incorporating measurements before and after the intervention. The study occurred during the competition season and included an 8-week training regimen with one session per week lasting approximately 22 min, totaling 174 min. PGs involved multiple players passing the ball, changing positions on the field after each pass, and preparing for the next pass without opposition. Creative performance was evaluated using the KORA (Konzeptorientiertes Expertenrating) and the game test situation taking advantage of openings, known for its ecological validity. Additionally, the effectiveness of passing and control was measured using the 2 vs. 2 game test. The results showed that eight PG sessions influenced the cognitive aspect of youth soccer players by enhancing tactical creativity and technical skills such as passing effectiveness. However, the intervention decreased ball control performance. This study confirms that trainers provide a valuable and diverse training approach to alleviate monotony. However, the approach must be adapted to the players' responses, and the complexity must increase accordingly.